2014
DOI: 10.1590/1806-9282.60.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mother-requested cesarean delivery compared to vaginal delivery: a systematic review

Abstract: The rates of c-sections without medical or obstetric indication have increased substantially in the last decades, especially in developing countries. Many factors contribute to this increase, being the mother-requested cesarean delivery a key contributing factor. There is a major debate about the implementation of c-sections performed at the mother's request without any established medical indication, and safety, cost, maternal autonomy, maternal and professional satisfaction, and ethics constitute important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Risks to the fetus and newborns should also be considered during the process of choosing the type of delivery in the absence of a medical indication for cesarean section. A review comparing cesarean section without medical indication and vaginal delivery has shown that cesarean section increases the risk of respiratory complications in the newborn 7 . Increases in cesarean rates have also been associated with higher rates of fetal mortality and a higher number of newborns admitted to a neonatal ICU for seven days or more, even after controlling for prematurity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Risks to the fetus and newborns should also be considered during the process of choosing the type of delivery in the absence of a medical indication for cesarean section. A review comparing cesarean section without medical indication and vaginal delivery has shown that cesarean section increases the risk of respiratory complications in the newborn 7 . Increases in cesarean rates have also been associated with higher rates of fetal mortality and a higher number of newborns admitted to a neonatal ICU for seven days or more, even after controlling for prematurity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as variáveis obstétricas, neste estudo o tipo de parto, a cesárea está associada a um maior desenvolvimento de condição aguda (97,7%) quando comparada ao parto por via vaginal. Uma revisão comparando a cesárea a pedido sem indicação médica e o parto vaginal mostrou que o parto cesáreo aumenta o risco de complicações respiratórias no RN (Bernardo, et al 2014).…”
Section: Resultsunclassified
“…Studies have been performed to evaluate possible associations among C-sections and maternal or neonatal morbidity and mortality. Considering morbimortality, C-section without clinical indication may be associated with increased risk of serious maternal (9) and neonatal outcomes (10), including respiratory complications in the newborn (11) and higher rates of fetal mortality (10). C-section also increases risks in future pregnancies, such as a higher frequency of abnormal placentation and rupture of the uterine scar.…”
Section: Introductionmentioning
confidence: 99%